2023
DOI: 10.1037/qup0000249
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and treatment of qualitative inquiry in general research methods textbooks.

Abstract: In contrast to an often-repeated and reductive story about the establishment of psychological research practices, the narrative of the field’s methodological development is unfolding, contentious, and situated within a wide range of historical developments. Such dynamism is evident in the recent ascension of qualitative inquiry. A new generation of researchers, scholars, and instructors are embracing methodological pluralism and qualitative inquiry, but their expectations may be incompatible with existing curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We raise concerns about the current state of psychological research which may disproportionately value a natural science paradigm. Psychology’s overreliance on a natural science paradigm has been demonstrated in psychology research methods textbooks in psychology and their coverage of the scientific method (J. C. Head et al, 2023).…”
Section: The Current State Of Qualitative Inquiry Within Psychologica...mentioning
confidence: 99%
See 2 more Smart Citations
“…We raise concerns about the current state of psychological research which may disproportionately value a natural science paradigm. Psychology’s overreliance on a natural science paradigm has been demonstrated in psychology research methods textbooks in psychology and their coverage of the scientific method (J. C. Head et al, 2023).…”
Section: The Current State Of Qualitative Inquiry Within Psychologica...mentioning
confidence: 99%
“…For example, not all qualitative studies are limited by a small sample size or by researchers’ biases, so it is sometimes inappropriate to report these as limitations (Levitt, Ipekci, et al, 2021). Additional metamethod and discursive work may examine how language is being used in methodological reporting and to represent qualitative paradigms (J. C. Head et al, 2023), especially given the lack of epistemological reporting observed by Rizo (2023).…”
Section: Recommendations For Transformative Futuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in 2018, the journal published a special issue titled “Teaching and Learning Qualitative Inquiry in Psychology at the Undergraduate Level,” which contained articles focused on topics such as curricula (McMullen & Winston-Proctor, 2018), pedagogy (Winston-Proctor, 2018), and apprenticeship (Neal Kimball & Turner, 2018). The journal also published a special section focused on award-winning qualitative dissertations (Josselson, 2020), as well as a special report focused on curricular resources for general methods courses (Head et al, 2023). Certainly, the journal is an invaluable resource for educators wishing to improve and expand the training of future qualitative researchers.…”
Section: Qualitative Psychology and The “Promises Of Qualitative Inqu...mentioning
confidence: 99%
“…The articulation of this promising vision occurred during a fortuitous period in which qualitative inquiry has been ascending within psychology (Head et al, 2023). This rise is evident in a variety of indicators: the availability of qualitative instructional materials has risen sharply in recent years (e.g., the 2021 book series tiled Essentials of Qualitative Methods ); the use of qualitative approaches and the publication of qualitative studies has increased (Hays et al, 2016; Levitt et al, 2018); publication and regulatory standards have become more inclusive of qualitative research (American Psychological Association [APA], 2015, 2016; Riley et al, 2019); psychology programs offering qualitative courses have increased (Levitt et al, 2018; Rubin et al, 2018); and programs have developed designated pathways for training in qualitative inquiry (Head & Daiute, 2021).…”
mentioning
confidence: 99%